Comparative Study between Full-Endoscopic Transforaminal Approach Lumbar Interbody Fusion (TF-LIF) Using PETLIF System and Minimally Invasive TLIF for Degenerative Lumbar Spine Disorders - Katsuhisa Yamada; Ken Nagahama; Hisataka Suzuki; Yuichiro Abe; Shigeto Hiratsuka; Yohei Sodeyama; Daisuke Ukeba; Hiroyuki Tachi; Tsutomu Endo; Takashi Ohnishi; Yuichi Hasegawa; Hideki Sudo; et al. (Spine Surgery and Related Research)
Introduction: To compare the clinical outcomes between a full-endoscopic transforaminal approach lumbar interbody fusion (TF-LIF) using the percutaneous endoscopic transforaminal lumbar interbody fusion (PETLIF) system and a minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). Methods: A total of 102 patients (80 females, 22 males; mean age: 70.0 years) with degenerative lumbar spine disorders who underwent PETLIF and were followed up for 2 years were assigned to the PETLIF group. Based on age, sex, and operated lumbar levels in the PETLIF group, 100 patients (71 women and 29 men; mean age: 68.9 years) who underwent MIS-TLIF were randomly selected and included in the MIS-TLIF group. This retrospective investigation included surgical data, radiographic assessment, and clinical outcomes. Results: The fusion rate was 95.1% and 96.0% in the PETLIF and MIS-TLIF groups, respectively (P=0.38). The decrease in hemoglobin levels from before surgery to 1 day after surgery was significantly lower in the PETLIF group than in the MIS-TLIF group (P<0.01). Five patients had detectable transient neurologic disorders after PETLIF that were resolved within 3 months. The increase in the local lordosis angle from before surgery to the final follow-up was significantly higher in the MIS-TLIF group than in the PETLIF group (P<0.01). Clinical scores were comparable between the two groups. Conclusions: Compared with MIS-TLIF, PETLIF showed excellent bone fusion rate and clinical outcomes. It was minimally invasive, resulting in less blood loss. However, exiting nerve root injury was a PETLIF-specific complication, and proper preventive management, including techniques to enlarge the Kambin's triangle, is required.